Seismic risk assessment as a basic tool for emergency planning: “Paces” EU project - Kazantzidou-Firtinidou, Danai; Gountromichou, Chrysa C.; Kyriakides, Nicholas; Liassides, Panagiotis; Hadjigeorgiou, Kyriakos (My University, 2017)
The main steps of the seismic risk assessment as essential tool of the risk management process are presented, highlighting the need of its standardization for the development of emergency plans by the civil protection authorities. Some of the available seismic risk assessment methods and outcomes are illustrated and demonstrated through a seismic scenario application for Heraklion city, capital of Crete in Greece. The scenario application is part of the European Project “PACES” (Preparedness for Appropriate Accommodation in Emergency Shelters), funded by DG-ECHO, which aims to improve preparedness for accommodation of evacuees after an earthquake in emergency shelters, based on realistic seismic scenarios. Different earthquake scenarios have been simulated based on local seismic hazard, reference to one of which is made herein. Semi-empirical methodology for the assessment of the structural vulnerability of the exposed assets has been applied, as well as published loss models for the evaluation of monetary and human losses. The risk maps will enable updating of existing earthquake emergency plans, and allow the mapping of possible locations for shelters and engraving of evacuation routes, as illustrated by the pilot study of Heraklion city. Moreover, possible areas for mass evacuation can be identified, and health-care, as well as the response capacities of other local and governmental agencies, will be assessed accordingly. Finally, future challenges for the evolution of the preparedness policy by means of the risk assessment are discussed.
Keywords: Casualties; Earthquake loss; Emergency planning; Emergency shelters; Evacuees; Preparedness; Risk management; Risk scenarios; Seismic risk assessment; Structural vulnerability